2021
DOI: 10.1371/journal.pone.0255635
|View full text |Cite
|
Sign up to set email alerts
|

Use of online resources by undergraduate medical students at College of Medicine, Majmaah University, Kingdom of Saudi Arabia

Abstract: The current pandemic has revolutionized medical education with a rapid shift to online teaching and learning strategies. The students have coped by turning to the online resources to keep pace with the change. To determine the type and practice of online resources used by undergraduate medical students and compare the use of online resources with gender and GPA. This was a cross-sectional study in which an online self-administered questionnaire was used to evaluate the type and practices of the online resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…The study's results showed that most PreCOVID and COVID students attended an average of 6 to 10 simulation sessions. This finding is similar to other studies conducted worldwide (Alabdulwahhab et al, 2021;Nisar et al, 2021;Thomas et al, 2020). In this study, more students in the COVID group participated in simulation sessions than in the PreCOVID group.…”
Section: Text Mining Of Open-ended Questionssupporting
confidence: 92%
“…The study's results showed that most PreCOVID and COVID students attended an average of 6 to 10 simulation sessions. This finding is similar to other studies conducted worldwide (Alabdulwahhab et al, 2021;Nisar et al, 2021;Thomas et al, 2020). In this study, more students in the COVID group participated in simulation sessions than in the PreCOVID group.…”
Section: Text Mining Of Open-ended Questionssupporting
confidence: 92%
“…One-fifth of the respondents used internet for searching literature for projects and lack of time was the barrier they faced in using the internet. A study conducted in Saudi Arabia by Alabdulwahhab et al (2021) assessed the use of online resources by undergraduate medical students at college of medicine, Majmaah University revealed that the majority of students' shifted to online resources during the pandemic. They used online free medical resources such as Medscape, Mayo Clinics, ResearchGate and MdWeb.…”
Section: Review Of Literaturementioning
confidence: 99%
“… 1 Despite there is increasing evidence in documented the effectiveness of e-learning during the COVID-19 pandemic in Saudi medical schools. 8 , 14 16 There is a lack of information about medical students’ perspective regarding e-learning at the University of Bisha, Southern Saudi Arabia. 17 Therefore, the present study aimed to evaluate medical students’ experience with OeL regarding satisfaction, communication enhancement, and intellectual environment.…”
Section: Introductionmentioning
confidence: 99%